Interactions between titanium dioxide nanoparticles and polyethylene microplastics: Adsorption kinetics, photocatalytic properties, and ecotoxicity. (July 2023) - Kalčíková, Gabriela; Roy, Rajdeep; Klun, Barbara; Rozman, Ula; Marolt, Gregor; Skalar, Tina; Feckler, Alexander; Bundschuh, Mirco
Abstract: The present study investigated the adsorption mechanism of titanium dioxide nanoparticles (nTiO2 ) on polyethylene microplastics (MPs) and the resulting photocatalytic properties. This effort was supported by ecotoxicological assessments of MPs with adsorbed nTiO2 on the immobility and behaviour of Daphnia magna in presence and absence of UV irradiation. The results showed that nTiO2 were rapidly adsorbed on the surface of MPs (72% of nTiO2 in 9 h). The experimental data fit well with the pseudo-second order kinetic model. Both suspended nTiO2 and nTiO2 immobilized on MPs exhibited comparable photocatalytic properties, with the latter showing a lower effect on Daphnia mobility. A likely explanation is that the suspended nTiO2 acted as a homogeneous catalyst under UV irradiation and generated hydroxyl radicals throughout the test vessel, whereas the nTiO2 adsorbed on MPs acted as a heterogeneous catalyst and generated hydroxyl radicals only locally and thus near the air-water interface. Consequently, Daphnia, which were hiding at the bottom of the test vessel, actively avoided exposure to hydroxyl radicals. These results suggest that the presence of MPs can modulate the phototoxicity of nTiO2 – at least the location at which it is active – under the studied conditions. Graphical abstract: Image 1 Highlights: Titanium dioxide nanoparticles (nTiO2 ) were rapidly adsorbed on microplastics (MPs). The experimental data fit well with the pseudo-second order kinetic model. Both suspended nTiO2 and nTiO2 immobilized on MPs were photocatalytic. Adsorption of nTiO2 on MPs reduced the UV-induced toxicity of nTiO2 .